Digit ratio and prosocial behavior the role of innate aggression in public goods and trust games - Guinto, Jahm Mae E. (Philippine Review of Economics, 2019)
Following previous studies that found individuals with shorter index fingers relative to ring fingers (low digit ratio) exhibit aggressive behavior in adulthood, in this study we use the left digit ratio, a putative marker for in-utero testosterone exposure [Manning et al. 1998], as an indicator of predisposition towards aggression to investigate its relation to prosocial behavior in the context of economic games. First, we ask if aggressive individuals and not-aggressive ones inherently differ in their prosocial behavior, independent of the features of the game. Second, we ask if the differences in their initial or subsequent prosocial behavior, if any, are conditioned by their respective experiences as the game progresses. Applying regression analyses on sample observations from two classroom experiments of modified public-goods games and trust games (by Carlos and Marasigan [2017] and Amante and Daro [2018], respectively), our results show that innate aggression per se is not associated with prosocial behavior. We find some evidence that innately aggressive, prosocial players who have experienced unfavourable or unfair outcomes in previous rounds tend to punish more intensely the non-cooperative players in public goods games, but continue to be generous towards selfish co-players in trust games. Thus, we posit that aggressive individuals who want to establish their perceived dominance (status) in a team behave prosocially initially, then later either elicit the cooperation of other players through aggressive punishment in the public goods game or unilaterally improve social welfare even at a personal cost to them in the trust game.